Effect of Cyclic Heat Treatment on Microstructure Evolution of TA15 Titanium Alloy - Dan-Ya Zhang; Zhi-Sheng Nong; Tian-Xing Wang (Archives of Metallurgy and Materials, 2023)
To investigate the effect of cyclic heat treatment on the microstructure evolution of titanium alloys, TA15 alloys were subjected to different numbers of heat treatment cycles at various temperatures in the (α + β) two-phase region. The resulting microstructure and hardness of the alloy were characterized by using the metallographic microscopy, scanning electron microscopy, and Vickers hardness testing. The morphology of the initial TA15 alloy was nearly equiaxed structure. The α phase content, thickness of the oxygen-rich α layer, and hardness of the TA15 alloy increased with the number of cycles. The morphology of the TA15 alloy changed into the Widmannstatten structure when the alloy underwent six cycles of heat treatment between 970 and 800°C. The thickness of the oxygen-rich α layer and hardness of the alloy increased with the lower limit temperature of the cyclic heat treatment. Compared with the number of cycles, the lower limit temperature of the cyclic heat treatment was a more significant factor on the microstructure evolution of the TA15 titanium alloy.